COOKIES SUBSTITUSI PUREE BAYAM HIJAU DAN TEPUNG KACANG HIJAU SEBAGAI CAMILAN TINGGI PROTEIN DAN ZAT BESI UNTUK REMAJA PUTRI ANEMIA - Bahriyatul Ma'rifah; Laras Deana Eka Suci; Arwin Muhlishoh (Media Gizi Pangan, 2023)
Adolescent girls are one of the groups that are vulnerable to nutritional problems, one of which is anemia. Anemia is characterized by the number of red blood cells or hemoglobin less than the normal limit of 12 g/dl. The incidence of anemia in adolescent girls is caused by a lack of knowledge regarding foods containing iron. One of the foods that contain high iron is green spinach puree and mung bean flour. This research was aimed to analyze the effect of substitution of green spinach puree and mung bean flour on the organoleptic quality and nutritional content of cookies. Pre-experimental research with Completely Randomized Design (CRD), using 4 composition ratios of wheat flour, mung bean flour and green spinach puree with ratios F0 (100% : 0% : 0%), F1 (75% : 20% : 5%), F2 (50% : 40% : 10%), and F3 (25% : 60% : 15%). The organoleptic test was evaluated using 30 semi trained panelists. Statistical analysis of the organoleptic test used the Kruskal Wallis test and Mann Whitney further test, while the nutrient content test used the Independent T Test. The substitution of green spinach puree and mung bean flour had a significant effect (p<0,05) on water content, ash, fat, protein, carbohydrates, iron, color, taste, and aroma. However, it did not have a significant effect on the hedonic texture test, and aftertaste (p>0,05) cookies .Cookies with the best formulation at F2 had 19,43 kcal of energy, 47,05 g of protein, 16,30 g of fat, 15,90 g of carbohydrates, and 34,82 mg of iron per serving of 60 g (3 pieces). Green spinach puree and mung bean flour substitution cookies have met the RDA for teenage girls aged 10-18 years. Cookies F2 can be claimed as a food product high in protein and iron and can be used as alternative snack for anemic adolescent girls.